ENVIRONMENTAL HEALTH RISK ANALYSIS OF CARBON MONOXIDE GAS EXPOSURE AMONG TRADERS OF GIWANGAN TERMINAL, YOGYAKARTA - Ahmad Faizal Rangkuti; Musfirah Musfirah; Yolanda Pridiana (Universitas Airlangga, 2022)
Introduction: The characteristics of CO gas are that it has no color, odor, and taste resulting from incomplete combustion, which accounts for 70% of motorized vehicle-related air pollution. Terminal traders are among those who are vulnerable to pollution caused by motorized vehicles. The study's goal was to determine the environmental health risk analysis of CO gas exposure to traders at Yogyakarta's Giwangan Terminal. Methods: This study was quantitative using a cross-sectional design study with the Environmental Health Risk Analysis (EHRA) approach. This study used purposive sampling technique. The population was traders, with a sample of 51 respondents. The research instrument is a questionnaire. The Chi-square test was used to measure the bivariate analysis data. Results and Discussion: The average concentration of CO gas was 0.9523 mg/m³, exposure duration was 12.1 hours/day, exposure frequency was 339.94 days/year, exposure duration was 11.96 years, and inhalation rate was 4.1 m³/o'clock. The highest abnormal blood pressure was 40 respondents. Real-time intake min. 0.0184 mg/kg/day, max. 3.0919 mg/kg/day (arrival), real-time intake min. 0.0190 mg/kg/day, max. 3.2021 mg/kg/day (departure). A total of 43 traders had a risk quotient (RQ) > 1. Conclusion: There was a relationship between the intake and the RQ of CO gas exposure but no relationship between blood pressure and the RQ due to CO gas exposure to traders at the Giwangan Terminal, Yogyakarta.